Islamic Performance Index for Measuring Compliance Performance in Islamic Banks (A Study of Bank Syariah Indonesia) - Istutik Istutik; Hedher Tuakia (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the compliance performance of Islamic banks using the Islamic Performance Index (IPI). The Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), and Islamic Income Ratio (ISIR) were selected to measure this performance. Bank Syariah Indonesia, as the largest Islamic bank in Indonesia, was selected as the object of the study, and data was taken from its 2021-2024 annual report. The results show that Bank Syariah Indonesia's PSR and ZPR continued to increase from 2020-2024, while its ISIR continued to decline. This explains that Bank Syariah Indonesia is allocating more of its financing to profit-sharing financing, with a proportion of 44.5%. Its social contribution to the community is increasing because zakat payments increased to 0.06% of total assets. Furthermore, non-halal income is decreasing to only 0.01%. Compliance with Sharia principles and BSI's attention to social aspects will increase public trust.